Selected Recent Institutional and Rule-Making Developments in the Law of the Sea (2015-2016) - Sipalla, Humphrey S (Strathmore Law Journal, 2016)
The United Nations Convention on the Law of the Sea (LOSC or the Convention) is quite simply, the greatest treaty-making achievement of the United Nations (UN) era. This appraisal of the recent developments of 2015-16 in this legal regime that governs the oceans – waters, floor and subsoil thereof – which cover ‘over 70 percent of the surface of our planet’, focuses on its oft-ignored spect, that is, its institutional framework.